Diversity And Enzyme Production From Lignocellulose-Degrading Bacteria In Soil From Penang Landfill - Bose, Chukwuma Ogechukwu (2024)
Lignocellulosic biomass has become a very appealing energy source to produce energy when compared to using food crops. Research is focusing on developing processes and technologies that can use this biomass to produce valuable polymers and energy instead of using expensive and exhaustible fossil sources. Lignocellulolytic enzymes act as biocatalysts that breakdown lignocellulose into its components for further hydrolysis into useful products. The study was done to provide extensive characterization and identification of lignocellulolytic bacteria in an environment that has been sparing studied for the purpose of discovering bacteria with lignocellulolytic potential for future applications. Another objective was to screen the bacteria for multi-enzymatic suitability in lignocellulose-driven refinery, and then generate information and recommendations for designing future consortia for the complete degradation of lignocellulose in the future. Culture independent study was carried out using metagenomic methods to determine the bacterial diversity of municipal solid waste sediments after DNA extraction and Polymerase chain reactions. Culture dependent methods formed the basis of isolating and screening bacteria from the same environment to identify potential bacteria that exhibit multi-enzymatic activity. Kinetic studies were then carried out using the growth rate and doubling time of bacterial isolates in lignin and starch as the criteria for selection. Qualitative studies using various cellulolytic media were used to further screen candidates. Phylogenetic analysis was conducted using the 16S rRNA sequences of the bacterial isolates.